2011
DOI: 10.1002/nau.21222
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of right frontal hypoperfusion and urinary dysfunction in iNPH: A SPECT study

Abstract: Urinary dysfunction was found to be closely related with right frontal hypoperfusion in iNPH using [(123) I]-IMP SPECT. This right frontal area is one of the critical areas for regulating micturition. While secondary incontinence can result from gait disturbance or dementia, there may also be a neurogenic mechanism underlying urinary dysfunction, which is a significant burden in patients with iNPH and their caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 35 publications
1
29
1
Order By: Relevance
“…On the other hand, patients with iNPH have the opportunity to improve LUTD with appropriate CSF shunt surgery. Sakakibara et al employed using [123I]‐iodoamphetamine (IMP)‐single‐photon emission CT (SPECT) and reported that iNPH patients with severe urinary frequency and incontinence showed significantly decreased right frontal hypoperfusion compared with the patients with mild symptoms . This study compared brain blood perfusion in NPH patients with improved LUTD after shunt surgery to those without LUTD improvement after surgery, and it demonstrated that the patients with LUTD improvement after surgery showed a significant increase in bilateral mid‐cingulate parietal and left frontal blood flow compared with those without improvement.…”
Section: Discussioncontrasting
confidence: 54%
“…On the other hand, patients with iNPH have the opportunity to improve LUTD with appropriate CSF shunt surgery. Sakakibara et al employed using [123I]‐iodoamphetamine (IMP)‐single‐photon emission CT (SPECT) and reported that iNPH patients with severe urinary frequency and incontinence showed significantly decreased right frontal hypoperfusion compared with the patients with mild symptoms . This study compared brain blood perfusion in NPH patients with improved LUTD after shunt surgery to those without LUTD improvement after surgery, and it demonstrated that the patients with LUTD improvement after surgery showed a significant increase in bilateral mid‐cingulate parietal and left frontal blood flow compared with those without improvement.…”
Section: Discussioncontrasting
confidence: 54%
“…Many neural tracts from the frontal lobe, such as thalamocortical tracts between the thalamus and the prefrontal cortex, the corticoreticulospinal tract, and the neural tract for urinary control, are known to pass through the anterior CR [28][29][30][31]. Furthermore, several authors have reported that patients with hydrocephalus exhibit clinical manifestations related to frontal lobe dysfunction with respect to cognition, gait, and urinary control [1,2,[32][33][34][35][36]. Accordingly, our finding that the anterior CR was most compressed by hydrocephalus might also be related to these clinical manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…Recent perfusion studies with single photon emission tomography revealed that a hypoperfusion was present in the right frontal area in INPH patients with moderate or severe incontinence, compared to those with none or mild incontinence [20]. …”
Section: Reviewmentioning
confidence: 99%